2005
DOI: 10.1038/sj.pcan.4500780
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic amines and genotype of N-acetyltransferases as risk factors for prostate cancer

Abstract: A variety of carcinogenic heterocyclic amines are produced during the cooking of meat at high temperatures. These carcinogens are metabolized by Nacetyltransferases (NAT), which are polymorphic in the population. This study examined associations between prostate cancer (PCa) and the consumption of different kinds of meat, heterocyclic amine intake and NAT genotypes. PCa patients and controls were recruited in the Syracuse, NY area. Levels of meat and heterocyclic amine intakes were determined from validated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
2
43
1
1
Order By: Relevance
“…At high doses, PhIP has been shown to act as a prostate carcinogen in rodent models (9), but DiMeIQx and MeIQx are thought to be more potent mutagens (28) than PhIP, so it is difficult to determine which might have more biological effect. In addition, few epidemiologic studies have evaluated these mutagens with consistent results; two previous case-control studies found no association for these heterocyclic amines (11,12), whereas one large study found a significant elevated risk for those in the highest category of PhIP intake but not DiMeIQx or MeIQx (13). In agreement with the previously reported cohort study (13), we did not find any association between BaP and prostate cancer.…”
Section: Meat Intake and Prostate Cancer Risk Cancer Epidemiol Biomarsupporting
confidence: 82%
See 1 more Smart Citation
“…At high doses, PhIP has been shown to act as a prostate carcinogen in rodent models (9), but DiMeIQx and MeIQx are thought to be more potent mutagens (28) than PhIP, so it is difficult to determine which might have more biological effect. In addition, few epidemiologic studies have evaluated these mutagens with consistent results; two previous case-control studies found no association for these heterocyclic amines (11,12), whereas one large study found a significant elevated risk for those in the highest category of PhIP intake but not DiMeIQx or MeIQx (13). In agreement with the previously reported cohort study (13), we did not find any association between BaP and prostate cancer.…”
Section: Meat Intake and Prostate Cancer Risk Cancer Epidemiol Biomarsupporting
confidence: 82%
“…Two small case-control studies found no association between PhIP or other major heterocyclic amines and prostate cancer (11,12), whereas a prospective study, with a larger sample size, found a significant 1.22-fold increased risk of prostate cancer for individuals in the highest quintile of PhIP intake (13). Only one previous epidemiologic study has evaluated the association between benzo(a)pyrene (BaP) from meat, a marker of PAH intake, and prostate cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…25 Also human prostate epithelial cells express NATs and are capable of activating heterocyclic amines. 26 In addition, the NER genes, ERCC1, 3, 5, 6 and XPC genes are expressed in the prostate 11 and prostate cells have also been shown to possess the ability to activate both polycyclic aromatic hydrocarbons and heterocyclic aromatic amines. 2 While several studies have examined NAT genes and prostate cancer risk, there is a lack of consensus on their role and impact on the disease, 9,26,27 which is likely because of variability in environmental exposures and allele frequencies across populations.…”
Section: Discussionmentioning
confidence: 99%
“…One allele of the NAT1 gene, NAT1*10, has been associated with an increased risk for a number of different cancers, including cancer of the prostate (16)(17)(18). In some studies, this allele leads to an elevation in enzyme activity, in particular tissues such as the colon and bladder (19).…”
Section: Introductionmentioning
confidence: 99%